The Influence Of Self-Confidence On Mathematical Problem Solving Ability Of Senior High School in Indonesia - Nizami, Ahmad Wafa; Ibupoto, Mukhtiar Hussain (Tematik : Jurnal Konten Pendidikan Matematika, 2024)
The objective of this study is to assess the level of self-confidence and mathematical problem-solving abilities among eighth-grade students at SMPN 1 Gending, as well as to determine whether self-confidence affects their mathematical problem-solving abilities. The study employs quantitative research methods and focuses on the entire population of eighth-grade students at SMPN 1 Gending. A total of 69 students were selected as research participants using the simple random sampling technique. Data were collected through questionnaires, essay questions, and documentation. The collected data were analyzed using simple linear regression analysis, with a significance level set at 5%. The findings of the data analysis indicated that the average self-confidence level fell within the medium category, specifically at 52.17%. Likewise, the average mathematical problem-solving abilities of the students were also categorized as medium, with a value of 50.73%. The results of the simple linear regression test revealed a significance value of 0.00, which is less than 0.05. Consequently, it can be concluded that self-confidence significantly influences students' mathematical problem-solving abilities. The study further showed that self-confidence had a 76.2% impact on students' ability to solve mathematical problems, while the remaining 23.8% was influenced by other factors.